2021
DOI: 10.30525/2256-0742/2021-7-5-114-122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Covid-19 Pandemic on the Industrial Sector: Implications for Economic Policy

Abstract: The COVID-19 pandemic had a major impact on the economy around the world, damaging many areas of daily life. The industrial sector has been affected by the effects of industrial closures, reduced economic activity, and disruptions in logistics and transportation. The damage caused by the crisis has not yet been specifically assessed, as the industrial sector was not the most affected by the pandemic compared to other sectors of the economy. The subject of the study is the industrial sector of Ukraine and the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Retail sales fell, except for food and beverages. Lebedeva and Moskalenko [46], using Ukraine as an example and 2020 data, found that industries such as car manufacturing, leather production, light industry, furniture manufacturing, coal mining, and oil and gas extraction were most affected. De Vet et al [47] examined industrial production in the EU27.…”
Section: The Impact Of Covid-19 On Business and Social Lifementioning
confidence: 99%
“…Retail sales fell, except for food and beverages. Lebedeva and Moskalenko [46], using Ukraine as an example and 2020 data, found that industries such as car manufacturing, leather production, light industry, furniture manufacturing, coal mining, and oil and gas extraction were most affected. De Vet et al [47] examined industrial production in the EU27.…”
Section: The Impact Of Covid-19 On Business and Social Lifementioning
confidence: 99%
“…COVID-19 pandemic has become the most serious test for the countries of the world in the last 150 years (Lebedeva, Moskalenko, 2021).…”
Section: Macroeconomic Dynamics and Industrial Lending: The Impact Of...mentioning
confidence: 99%
“…[16][17][18] Conversely, the slowdown in manufacturing activities due to lockdowns resulted in reduced demand for chemicals used in non-essential industries, such as construction and automotive. [19][20][21][22][23][24][25] Moreover, the pandemic had profound implications for the chemical industry's workforce. Ensuring the safety and well-being of employees in chemical plants and facilities became a top priority, leading to the implementation of stringent health protocols and safety measures.…”
Section: Introductionmentioning
confidence: 99%
“…With the healthcare sector under immense pressure to secure medical supplies, disinfectants, and pharmaceuticals, certain chemicals experienced an unprecedented surge in demand 16‐18 . Conversely, the slowdown in manufacturing activities due to lockdowns resulted in reduced demand for chemicals used in non‐essential industries, such as construction and automotive 19‐25 …”
Section: Introductionmentioning
confidence: 99%